Gender inequalities among adults and children in collective households - Lucia Mangiavacchi; Luca Piccoli (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper studies the distribution of resources within Albanian families in 2012 using a collective consumption model with two alternative specifications: the first enables the estimation of intrahousehold distribution of resources among male adults, female adults and children; the second extends the analysis to girls and boys. To improve the identification in the context of extended families we implement a strategy to identify the main decision making couple within the household. In line with previous evidence on gender discrimination in Albania, the results show that the female shares of resources are substantially lower with respect to a fair distribution, and that sons receive a larger share of resources than daughters. We further explore whether the migration experience of the husband of the main couple influences the distribution of resources within the family and find evidence that the time spent abroad by the male migrant increases gender inequality (by increasing the share of men more than that of women) and worsen children's position, both when the family was left behind and when also women and children joined the migrant in the destination country.
Keywords: D13; H31; I32; O15; 330; gender inequalities; intrahousehold distribution; collective consumption models; international migration; Albania